Recognition of Gallotannins and the Physiological Activities: From Chemical View - He, Hua-Feng (Frontiers in Nutrition, 2022)
Gallotannins, characterized with the glycosidic core and galloyl unit, are seemed as vital components of hydrolyzable tannins. Benefit from the more and more discoveries of their bioactivities and edibility, application of gallotannins in food industry, pharmacy industry, and other fields is increasing. Inheriting previous study achievements, chemical structure of gallotannins was illustrated and degradation as well as synthetic routes to gallotannins were summarized. On this basis, distribution in the nature also including the distinction of gallotannins was discussed. More than that, activities involving in antioxidant, anti-inflammatory, enzyme inhibitions, protein binding, and so on, as well as applications in the field of food industry, biopharmaceutical science, agricultural production, etc., were combed. Finally, improvement of bioavailability, chemical modification of the structure, and accurate determination of new gallotannins were pointed out to be the orientation in the future.